A new software development for Fuzzy Multicriteria decision‐making - Güvenç Arslan; Özlem Aydın (Technological and Economic Development of Economy, 2009)
In this paper, software for Fuzzy Multiple Criteria Decision Making (FMCDM) problems has been developed and tested on two real problems. FMCDM methods are widely used when imprecise data or linguistic variables exist in the problem. Using FMCDM methods may help improve decision‐making problems and lead to more accurate models. Although these methods are more involved in terms of computing due to fuzzy calculations in MCDM algorithms, fuzziness offers advantages over classical algorithms. Thus appropriate software is of great importance in applying FMCDM methods. The major aim of this study is to develop software and to test it on two real military problems which are solved by an ideal points algorithm and an outranking method. The results and outputs are discussed with sensitivity analyses.